Structural and Morphological Properties of Ultraluminous Infrared Galaxies at 1 < z < 3 - Fang Guanwen; Ma Zhongyang; Chen Yang; Kong Xu (Open Astronomy, 2015)
Using the Hubble Space Telescope (HST)/Wide Field Camera 3 (WFC3) near-infrared high-resolution imaging from the 3D-HST survey, we analyze the morphology and structure of 502 ultraluminous infrared galaxies (ULIRGs; LIR > 1012L⊙) at 1 < z < 3. Their rest-frame optical morphologies show that high-redshift ULIRGs are a mixture of mergers or interacting systems, irregular galaxies, disks, and ellipticals. Most of ULIRGs in our sample can be roughly divided into merging systems and late-type galaxies (Sb−Ir), with relatively high M20 (> −1.7) and small Sérsic index (n < 2.5), while others are elliptical-like (E/S0/Sa) morphologies with lower M20 (< −1.7) and larger n (> 2.5). The morphological diversities of ULIRGs suggest that there are different formation processes for these galaxies. Merger processes between galaxies and disk instabilities play an important role in the formation and evolution of ULIRGs at high redshift. In the meantime, we also find that the evolution of the size (re) with redshift of ULIRGs at redshift z ∼ 1 ∼ 3 follows the relation re ∝ (1 + z)−(0.96±0.23).